SMART ROBOTS ON THE JOB: MAKING FACTORIES AND SHOPS RUN SMOOTHLY - Komilova Hilola (Web of Journals Publishing, 2025)
This study investigates the role of smart robots in enhancing operational efficiency in factories and retail shops, addressing the limitations of traditional labor-intensive processes. By leveraging artificial intelligence (AI), robots optimize productivity, reduce costs, and foster human-robot collaboration. A mixed-methods approach, including surveys and case studies, examines the impact of robots on workflow efficiency and worker satisfaction. Findings reveal significant improvements in production speed and error reduction, though challenges like training needs persist. The study contributes to industrial automation by offering insights for integrating smart robots in diverse settings.
Keywords: Smart robots, industrial automation, factory efficiency, retail optimization, human-robot collaboration